Preventive effect of bentonite against pyoderma via direct binding capability of staphylococci - Mao Kaneki; Chiharu Ohira; Miyu Takahashi; Tomoki Fukuyama (PLoS ONE, 2026)
Bentonite, a naturally occurring clay mineral, is widely used for detoxifying mycotoxins and chemical contaminants, yet its potential interactions with microorganisms remain poorly characterized. Staphylococci, including Staphylococcus aureus in humans and Staphylococcus pseudintermedius in dogs, are major contributors to impetigo or pyoderma and other skin diseases, with rising antibiotic resistance underscoring the need for novel preventive strategies. This study investigated whether sodium bentonite directly modulates staphylococcal growth and associated inflammatory responses in vitro and in vivo . In bacterial culture assays, sodium bentonite showed a strong binding affinity for staphylococci, leading to significant reductions in viable colony counts. Pre-treatment of S. aureus and S. pseudintermedius with bentonite attenuated keratinocyte injury and markedly suppressed pro-inflammatory cytokine secretion, including IL-6, IL-8, and CCL2. In a murine pyoderma model, bentonite pre-treatment of S. pseudintermedius prevented lesion development, reduced bacterial burden, and downregulated cutaneous expression of TNFα, IL-1β, and IL-13, findings that were corroborated by histological improvements. Importantly, these effects extended to methicillin-resistant strains, highlighting a potential application against drug-resistant staphylococcal infections. By contrast, direct topical administration of bentonite gel in a murine atopic dermatitis model produced only modest benefits: ear swelling was reduced, but transepidermal water loss and clinical scores remained unchanged, suggesting limited therapeutic value in established chronic inflammatory conditions. Overall, sodium bentonite does not exhibit intrinsic bactericidal or anti-inflammatory properties but exerts protective effects through direct bacterial binding and subsequent inhibition of staphylococcus-induced cytotoxicity and inflammation. These findings identify sodium bentonite as a safe, non-antibiotic preventive option for staphylococci-associated skin diseases, particularly pyoderma, in both humans and companion animals. Future studies should further explore formulation strategies and delivery methods to optimize its clinical utility.